MERDEKA BELAJAR IN PANDEMIC: USING QUIZIZZ GAME BASED LEARNING TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Maria Dimitrij Angie Pavita; Deli Nirmala Nirmala (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
Pandemic of Covid-19 has made teaching and learning process change from conventional into digital. With “Kurikulum Merdeka Belajar” teachers can choose any learning method which allows more innovation. The purpose of this study is to improve students' vocabulary mastery through Quizizz. This study was an action research project.  The research was conducted at SMA Bruderan Purwokerto.  The subject of the research was twenty-six students of X MIPA 1. The research was done in two cycles. There were four steps in each cycle. They were planning, action, observation, and reflection. The result shows that the students’ vocabulary mastery is improving. When the pre-test is compared to the post-test, the mean score increases significantly, from 64 to 85. Beside the cognitive ability improves, the affective factors of the learners improve. This is due to their enjoyment and easiness of memorization. Quizizz can be one of the learning media that can make the students more enjoyable in learning English especially vocabulary since the students can memorize and get new vocabulary much easier.